Turmeric flour supplementation in feed to improve goldfish performance - Kartina, Kartina; Awaludin, Awaludin; Andika, Andika (Arwana: Jurnal Ilmiah Program Studi Perairan, 2024)
Goldfish (Carassius auratus) is an ornamental fish that is widely loved and has good prospects for development. This study aims to improve the growth of goldfish (Carassius auratus) fed with feed enriched with turmeric flour. The test fish used were goldfish seeds (Length 3-4 cm and weight 2-3 g). This study was an experimental study with a completely randomized design (CRD) consisting of 4 treatments and three replications consisting of commercial feed (P0), feed enriched with turmeric flour with a dose of 1% (P1); 2% (P2) and 3% (P3). The results showed that adding turmeric flour to the feed statistically significantly affected the seeds’ absolute weight and Specific Growth Rate (SGR). Still, they were not significantly different in the seeds’ absolute length value, Fed Conversion Ratio (FCR), and Survival Rate (SR). Treatment with a dose of 3% showed the best value in absolute weight of 4.66 ± 0.23 g, absolute length of 2.93 ± 0.12 cm, SGR of 2.68 ± 0.15%, FCR of 1.41 ± 0.03, and feed protein content (50.04%). Turmeric flour has the potential to be used as a supplement in feed because it can increase feed protein content and seed growth and reduce FCR values ​​better than without the addition of turmeric flour.